(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Human Resource Management (HRM) is the phrase used to define structured processes developed within an organization for handling employees. A human resource manager’s duties fell into three primary areas personnel, workplace pay and benefits, and work definition design. Essentially, HRM’s goal is to optimize an organization’s profitability by maximizing its employee effectiveness. Given the fast growing rate of transition in the corporate environment, this policy is unlikely to shift in any significant way. The fundamental goal of human resources must often be to attract, grow and maintain talent match the staff with the enterprise and be an outstanding asset to the company. Such three tasks will never alter. Human Resource Management may be a concern particularly for small companies, who usually have no HR department on which to focus. They may be restricted to one HR person or the CEO may still have the duty. Nonetheless, small business manager has to consider the threats that confront them in order to be able to tackle HR problems as their organization and workforce expands. The purpose of this paper is to research the challenges in HRM, suggest measures to overcome the challenges and highlight the emerging challenges in HRM.